Audit quality weakens earnings management effect on company value - Rondonuwu, Kezia Hany Josefin; Suhartono, Sugi (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2023)
Managers frequently use earnings management techniques to boost company value by making financial reports appear good to investors. Because of this earnings management, investors may choose the wrong investments, and share prices may fall that lowering the company's worth. Theoretically, audit quality can minimize earnings. Yet, whether audit quality can reduce the impact of earnings management on company value has not been clearly disclosed. This study aims to provide an answer to this topic by applying the agency theory, signal theory, and market efficiency theories. Companies in the primary consumer goods industry that list on the Indonesia Stock Exchange (IDX) in 2018–2020 are the objects used. 141 businesses in total were chosen as samples using the purposive sampling methodology. The study's use of moderated regression analysis (MRA) demonstrates that earnings management has a detrimental impact on business value. Additionally, it was discovered that the detrimental impact of earnings management on firm value might be mitigated by audit quality. Practically, this study confirms that the use of reputable auditors can minimize earnings management and protect against a decline in firm value. Subsequent research can examine whether a company's reputation can reduce public suspicion of earnings management. Plagiarism Check